Prevalence of back pain among pregnant women attending public health center in west Lampung, Indonesia - Siska Widiyastika; Aryanti Wardiyah; Rilyani Rilyani (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Pregnant women throughout Indonesia are 60-80 percent of pregnant women who experience back pain during pregnancy. The prevalence of pregnant women experiencing low back pain in various regions of Indonesia reaches 60-80 percent. Data from the results of the pre-survey that had been conducted showed that the number of pregnant women at the Sugar Cane Health Center was 100 people, at the Gedung Surian Health Center 172 people, and at the Sumberjaya Health Center 115 people. Interviews were conducted with 10 pregnant women at the Kebun Tebu Health Center 70 percent of the 10 pregnant women experienced back pain during their pregnancy, 40 percent of them were over 30 years old, and 30 percent of them were first pregnancies (primiparous).Purpose: To determine the prevalence of back pain among pregnant women attending public health centers in west Lampung, IndonesiaMethod: This study uses a quantitative research type, with correlation analytic methods. The population in this study were pregnant women who were domiciled in the working area of the West Lampung Kebun Tebu Health Center with a total of 100 pregnant women. The sampling technique uses total sampling. Measurement of this study using a questionnaire. Data analysis used a frequency distribution test (univariate).Results: The prevalence of pain scale in this study was from 100 respondents who experienced mild pain as many as 55 respondents and those who experienced moderate pain as many as 30 respondents. There were 15 respondents who did not experience pain but none of the respondents experienced severe pain. And to get information about the treatment of back pain, among them, 60 respondents got information from their families and 40 respondents got information from health workers. However, none of the respondents obtained information from the Internet.Conclusion: the relationship between, gestational age, and TFU. BMI, TBJ, pain management, and information on pain management with back pain in pregnant women with a p-value <0.05.